Autonomes Fahren statt Stop and Go: Vorschläge zur effektiven Gestaltung der deutschen Kurzarbeit - Balleer, Almut; Gehrke, Britta; Hochmuth, Brigitte; Merkl, Christian (Perspektiven der Wirtschaftspolitik, 2019)
This article argues that short-time work stabilized employment in Germany substantially during the Great Recession in 2008/09. The labor market instrument acted in timely manner, as it was used in a rule-based fashion. In addition, discretionary extensions were effective due to their interaction with the business cycle. To ensure that short-time work will be effective in the future, this article proposes an automatic facilitation of the access to short-time work in severe recessions. This reduces the likelihood of a too extensive use at the wrong point in time as well as structural instead of cyclical interventions.
CRIS-Team Scopus Importer:2020-02-21

Counteracting unemployment in crises: Non-linear effects of short-time work policy - Gehrke, Britta; Hochmuth, Brigitte (Scandinavian Journal of Economics, 2019)

Hartz IV and the decline of German unemployment: A macroeconomic evaluation - Hochmuth, Brigitte; Kohlbrecher, Britta; Merkl, Christian; Gartner, Hermann (Journal of Economic Dynamics & Control, 2021)
This paper proposes a new approach to evaluate the macroeconomic effects of the “Hartz IV” reform, which reduced the generosity of long-term unemployment benefits. We propose a model with different unemployment durations, where the reform initiates both a partial effect and an equilibrium effect. We estimate the relative importance of these two effects and the size of the partial effect based on the IAB Job Vacancy Survey. Our approach does not hinge on an external source for the decline in the replacement rate for long-term unemployed. We find that Hartz IV was a major driver for the decline of Germany’s steady state unemployment and that partial and equilibrium effect were of equal importance. In addition, we provide direct empirical evidence on labor selection, one potential dimension of recruiting intensity.<br
Keywords: Unemployment benefits reform; Search and matching; Hartz reforms